Mitochondrial Dysfunction and Insulin Resistance in Pubertal Youth Living with Perinatally Acquired HIV - Gojanovich, Greg S. (AIDS Res Hum Retroviruses, 2020)
Mitochondrial dysfunction (MD) is linked to cardiometabolic complications, such as obesity and insulin resistance (IR), the frequencies of which are higher in adults living with HIV infection and receiving combination antiretroviral therapies (ARV). ARV-treated youth living with perinatally acquired HIV infection (YLPHIV) may be especially susceptible to IR due to long-term exposure to both factors. Medical histories, fasting blood chemistry panels, and mitochondrial function in banked peripheral blood mononuclear cells (PBMCs) were assessed in eligible YLPHIV from the Pediatric HIV/AIDS Cohort Study (PHACS)/Adolescent Master Protocol (AMP) Mitochondrial Determinants Component cohort, stratified by Homeostatic Model Assessment of IR (HOMA-IR) score: case (score ≥4, n = 39) or control (score <4, n = 105). PBMCs were sources for mitochondrial (mt) DNA copies/cell; mtRNA transcript levels of oxidative phosphorylation (OXPHOS) subunits NADH dehydrogenases 1 and 6, and cytochrome B; and enzymatic activities of OXPHOS Complexes I (CI) and IV (CIV). Logistic regression models were fit to estimate the odds of IR case diagnosis, adjusted for sex, race/ethnicity, body mass index (BMI) z-score, and Tanner stage. IR cases were similar to controls by age, sex, and race/ethnicity. Cases had higher median levels of peak HIV viral load, lactate, pyruvate, triglycerides, and BMI z-scores. OXPHOS CI enzymatic activity was lower in cases (log(10) 1.62 vs. 1.70) and inversely correlated with HOMA-IR score (r = −0.157, p = .061), but did not associate with IR in adjusted models. Fully adjusted models indicated associations of nadir CD4% [odds ratio (OR) = 0.95, 95% confidence intervals (CIs) = 0.90–1.00] or peak HIV load (OR = 3.48, 95% CIs = 1.70–10.79) with IR. IR in YLPHIV was strongly associated with morphometrics, but early virologic and immunologic factors may also influence MD.